دور نظم المعلومات الإستراتيجية في تنمية الميزة التنافسية في المؤسسة الإقتصادية دراسة حالة – مطاحن بلغيث الكبرى – مداوروش - سارة خرايفي; سلاف فارح (My University, 2021)
This study aims to highlight the role that strategic information systems plays in its two dimensions, organizational requirements and technological requirements in developing the Competitive advantage in its dimensions, leading the lowest cost, distinguishing Products and concentration in Balghaith Grand Mills Corporation - Madawroush-, and to achieve the objectives of the study, the questionnaire was relied on for the purpose of data collection, where the number of valid questionnaires For analysis (40) questionnaires, using the program (spss.v.23) to analyze data The questionnaire, we relied on the descriptive analytical method, and we have The study found that the sample's perceptions of the level of importance of strategic information systems And the level of competitive advantage were strong, and that technological requirements were occupied First place, followed by organizational requirements, with a small difference. As for least Cost leadership, it came in the first place, followed by concentration and then distinguishing Products , Hence the stratigic role of the information system sis to provide appropriate information on the various dimensions and environmental conditions that use of information technology in developing products and services that give the organisation a strategic experience that surpasses the competitive forces it faces in the markets, .............................................................. تهدف ىذه الدراسة إلى إبراز الدور الذي تلعبو نظم المعلومات الإستراتيجية ببعديها المتطلبات التنظيمية والمتطلبات التكنولوجية في تنمية الميزة التنافسية بأبعادىا قيادة التكلفة الأقل؛ تميز المنتجات والتركيز في مؤسسة مطاحن بلغيث الكبرى –مداوروش-، ولتحقيق أىداف الدراسة تم الإعتماد على الإستبانة لغرض جمع البيانات، حيث كان عدد الإستبانات الصالحة للتحليل ) 40 ( إستبانة، بإستخدام برنامج ) spss.v.23 ( لتحليل بيانات الإستبانة، إعتمدنا على المنهج الوصفي التحليلي، ولقد وجدت الدراسة أن تصورات العينة لمستوى أهمية نظم المعلومات الإستراتيجية ومستوى الميزة التنافسية كان قويا، وأن بعد المتطلبات التكنولوجية إحتل المرتبة الأولى يليو بعد المتطلبات التنظيمية بفرق بسيط، أما قيادة التكلفة جاءت في المرتبة الأولى يليها التركيز ثم التميز، ومن هنا فإن الدور الإستراتيجي لنظم المعلومات يتمثل في توفير المعلومات الملائمة على الأبعاد والظروف البيئية المختلفة التي تحيط بالمنظمة وأيضا إستخدام تكنولوجيا المعلومات في تطوير المنتجات والخدمات التي تعطي للمنظمة خبرة إستراتيجية تفوق القوى التنافسية التي تواجهها في الأسواق.